Oct4‐EGFP reporter gene expression marks the stem cells in embryonic development and in adult gonads of transgenic medaka12. Issue 1 (27th December 2012) - Froschauer, Alexander; Khatun, Mst. Muslima; Sprott, David; Franz, Alexander; Rieger, Christiane; Pfennig, Frank; Gutzeit, Herwig O.
Abstract Maintenance of pluripotency in stem cells is tightly regulated among vertebrates. One of the key genes in this process is oct4, also referred to as pou5f1 in mammals and pou2 in teleosts. Pou5f1 evolved by duplication of pou2 early in the tetrapod lineage, but only monotremes and marsupials retained both genes. Either pou2 or pou5f1 was lost from the genomes of the other tetrapods that have been analyzed to date. Consequently, these two homologous genes are often designated oct4 in functional studies. In most vertebrates oct4 is expressed in pluripotent cells of the early embryo until the blastula stage, and later persist in germline stem cells until adulthood. The isolation and analysis of stem cells from embryo or adult individuals is hampered by the need for reliable markers that can identify and define the cell populations. Here, we report the faithful expression of EGFP under the control of endogenous pou2/oct4 promoters in transgenic medaka (Oryzias latipes). In vivo imaging in oct4‐EGFP transgenic medaka reveals the temporal and spatial expression of pou2 in embryos and adults alike. We describe the temporal and spatial patterns of endogenous pou2 and oct4‐EGFP expression in medaka with respect to germline and adult stem cells, and discuss applications of oct4‐EGFP transgenic medaka in reproductive and stem cell biology. Mol. Reprod. Dev. 80: 48–58, 2013. © 2012 Wiley Periodicals, Inc.